2013
DOI: 10.7860/jcdr/2013/5309.3058
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Secretory and Anti- Ulcerogenic Activities of Avipattikar Churna on The Peptic Ulcers in Experimental Rats

Abstract: Background: Avipattikar churna, a poly-herbal formulation, is one of the popular ayurvedic formulations which is used for peptic ulcer diseases but the scientific documentation with regards to its effect for the indication is lacking. Aims:This study was carried out to evaluate the anti-secretory and the anti-ulcerogenic activities of the churna and to compare its activity with that of ranitidine in a pyloric ligated model of rats. Material and methods:Four groups of rats with 6 animals in each served as the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…To evaluated protective effects of geraniin on reflux esophagitis rats, experimental rats were orally administrated with geraniin (15 and 30 mg/ kg body weight) and H2 inhibitor ranitidine 30 mg/kg body weight as positive control. Ranitidine, a histamine-2 receptor antagonist, used as a reference drug in study of gastritis and clinical practice [24,25]. In damage area and histological analysis showed that the esophageal tissue of the RE control group indicated a tissue damages such as hemorrhage, inflammatory cell infiltration and epithelium destruction induced by reflux (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluated protective effects of geraniin on reflux esophagitis rats, experimental rats were orally administrated with geraniin (15 and 30 mg/ kg body weight) and H2 inhibitor ranitidine 30 mg/kg body weight as positive control. Ranitidine, a histamine-2 receptor antagonist, used as a reference drug in study of gastritis and clinical practice [24,25]. In damage area and histological analysis showed that the esophageal tissue of the RE control group indicated a tissue damages such as hemorrhage, inflammatory cell infiltration and epithelium destruction induced by reflux (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Lavang helps in maintaining the basal gastric mucosal blood flow and it increases the mucus secretion. [11] Kamdhudha Ras -its action can be seen right from Amashaya like it reduces heat of the stomach, reduces inflammation of the organs of the digestive system and lowers the tendency of bleeding. The main Karya of Kamdudha Ras is Pittashaman, Raktastambhan, Kshobhanashan and is Shitviryatmak.…”
Section: Discussionmentioning
confidence: 99%
“…Siddha makardvaja Rasa is good immune boosting drug used in RA [ 15 ] Aswagandha (Withenia somnifera) is a good Rasayana and showed promising antibacterial, anti-tumoral, immune-modulating, and anti-inflammatory properties [ 16 ]. Kaisara Guggulu has a good outcome in Vata ratka (Arthropathy) [ 17 ]and Avipatikar Churna is a good laxative and cyto-protective [ 18 , 19 ]. So the administrated regimen has pitta-vata nasaka (Anti pitta and vata) , jvara hara (anti-pyretic) , bedana nasaka (Analgesic) , anulomaka (Laxative) , and Rasayana (immunomodulation) properties.…”
Section: Discussionmentioning
confidence: 99%